Prática do acolhimento à pessoa idosa na atenção básica: uma estratégia de humanização - Alves, Selda Gomes de Souza (2009)
The aging of the population already is a fact, before considered a phenomenon, today, is part of the reality of the majority of the societies in the world. The present study it has as objective to analyze the practical one of the shelter developed for the team to multidiscipline for the elderly in the Strategy of Health of the Family. One is about a descriptive and exploratória inquiry, developed by means of quantitative boarding. The population of this study consisted of nineteen teams that work in the inserted ESF in the urban zone of the city of Sousa-PB, understanding a complete of 133 professionals. The collection of date was carried through through a questionnaire contends closed questions, referring to the partner-demographic date e, specific open questions. The main results indicate that the professionals of Health of the city of Sousa, PB, that had participated of this study had consisted in a complete of 76. Amongst these, 20% are nurses, followed of the odontólogos in 6%; 35% are ACS and technician of nursing with 19%. The age of the interviewed ones meets in the age band enters, 21 and 30 years, in 43%. The majority is of the feminine sex with a 84% total. Already in accordance with civil state 34% is married. If treating to the wage, the doctor has of greater of 12 wages. The participants present the percentile greater of formed time of with referring 33% of 1 the 3 years of formation. E finally, the changeable time of performance, if had detached 39% of the participants with 08 the 11 years. With regard to as if it processes the reception and attendance to the person in the ESF, we can observe that, with priority attendance was prominence with 27% of the participants, followed of a considerate attendance with 26%. Already in relation to the actions that are developed daily in the ESF, these they are come back toward the HIPERDIA with 40%, followed of actions ruled in orientation with 27%. Some actions they are carried through in accordance with the aged necessity of each (13%) and through visits domiciliary (9%). It was asked to them as the shelter was facilitated in the UBS, these had told that it is through the attention that is excused the aged one (35%), and finally, as this made it difficult age, in its majority with 37% they had not wanted to answer, followed of the lack of understanding with 26%. With this study it was possible to conclude that the practical one developed for the professionals of the ESF of the city of Sousa, PB with the elderly, is characterized by an assistance ruled in the clinical aspect, little focused in the actions that to permeate the PNH